Near and far: Tracing memory and reframing presence in pandemic-era Argentina. (June 2023) - Zaretsky, Natasha
Memory has been a central foundation of democracy and civil society in Argentina since the first years of the military dictatorship (1976–1983) when groups occupied public spaces to protest systematic disappearances and state repression that left 30, 000 victims. It has taken decades to achieve some form of justice for state terror and repression, much of that shaped by the culture of memory and accountability that hinged on embodied forms of public protest. But what happens to cultural memory when a pandemic precludes traditional forms of gathering? And what does this reveal about how Argentines renegotiate the significance of shared remembering and presence? Building on ethnographic fieldwork in Buenos Aires, this visual essay examines the significance of shared embodied practices of remembering through the lens of pandemic restrictions that invite new insights into the relationship between presence and political belonging. Rather than simply reacting to specific instances of injustice, this essay argues for the significance of cultural memory practices as fundamentally constitutive of democratic culture and civil society in Argentina as it faces new challenges.